RHETORIC AND THE FEMININE CHARACTER: CICERO’S PORTRAYAL OF SASSIA , CLODIA AND FULVIA - Ige, S. (Akroterion, 2012)
The role of women in the ancient world has been extensively debated and a significant amount of work has been done in this area. Included in the texts that have received attention are Cicero’s speeches which refer to women. All the women who feature in Cicero’s speeches were those who have been acknowledged to have made their presence felt in the Roman public domain. Although Roman society regulated its socio-political activities around masculine values, it is nevertheless difficult to explain why so few women appear in such a voluminous corpus like Cicero’s.1 What is certain is that Ciceronian rhetoric is characterised by the use of invective and vituperation.2 In this article, I shall argue that the women who were negatively portrayed in Cicero’s speeches were victims of an already standardised form of communication within the hegemonic male order that dominated the Roman public domain in first century BC.